Three new species of Elachista Treitschke (Lepidoptera: Elachistidae: Elachistinae) from Nepal - Sruoga, Virginijus (Zootaxa, 2008)
Three new species of Elachista Treitschke, E. ievae sp. nov., E. tuberella sp. nov. and E. obtusella sp. nov., from Nepal are described and illustrated. E. ievae is placed in E. gleichenella species group, E. tuberella and E. obtusella are placed in E. freyerella species group.